THE CENTRALIZED STRUCTURE OF FUND OF ASSESSMENT TOOLS OF EDUCATIONAL PROGRAM - Elena Yu. Shakhova; Elena V. Nester; Il’ya S. Sitov (Высшее образование в России)
Abstract. The centralized structure of assessment tools of the main educational program of higher education consists of the following documents:- fund of assessment tools of the educational program — the central document uniting information on competences (formulations, codes of competences, a matrix of competences, stages of formation of competences), the description of types and forms of control on all elements of the educational program, criteria and scales of estimation (basic, standard, specialized), the methodical materials defining procedures of assessment tools development and the procedure of assessment, the main assessment tools of elements of the educational program;- funds of assessment tools of the current control of progress and intermediate certification as a part of working programs for separate elements of the educational program, which are developed on the basis of a central document.The offered structure of the fund of assessment tools is brought closer to the classical scheme of normalization of data – «one fact – in one place». The basic information relating to competences is concentrated in one document. Distinctive feature of the offered structure is the possibility to reduce considerably time and labor input of documentation development of the educational program.